"If You Call Them, They Will Come": A Telephone Call Reminder to Decrease the No-Show Rate in an Outpatient Palliative Medicine Clinic. (May 2021) - Lagman, Ruth L.; Samala, Renato V.; LeGrand, Susan; Parala-Metz, Armida; Patel, Chirag; Neale, Kyle; Carrino, Cheryl; Rybicki, Lisa; Gamier, Pamela; Mauk, Mary Ellen; Nowak, Molly
Introduction: A high outpatient clinic no-show rate affects clinical outcomes, increases healthcare costs, and reduces both access to care and provider productivity. In an effort to reduce the no-show rate at a busy palliative medicine outpatient clinic, a quality improvement project was launched consisting of a telephone call made by clinic staff prior to appointments. The study aimed to determine the effect of this intervention on the no-show rate, and assess the financial impact of a decreased no-show rate. Methods and Materials: The outpatient clinic no-show rate was measured from September 1 to December 31, 2015. Data from the first 8 months of the calendar year was removed since these could not be verified. Starting January 1, 2016, patients received a telephone call reminder 24 hours prior to their scheduled outpatient appointment for confirmation. No-show rate was again measured for the calendar year 2016. Opportunity costs were calculated for unfulfilled clinic visits. Results: Of the 1224 completed visits from September 1 to December 31, 2015, 271 were no-shows with an average rate of 11.8%. After the intervention, there were 4368 completed visits and 562 no-shows. The no-show rate for 2016 averaged 6.9% (p < 0.001), down 4.9% from the last 4 months of 2015. Estimated opportunity costs were about 396 no-show visits avoided, equivalent to an annual savings of about 79, 200. Conclusion: A telephone call reminder to patients 24 hours prior to their appointment decreased the no-show rate in an outpatient palliative medicine clinic. Avoiding unfulfilled visits resulted in substantial opportunity costs.